Teori Belajar Behavioristik dalam Kitab Bughyatul Ikhwan Karya Imam Ramli - Aziz, Aba Agil; Muhid, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Behavioristic learning theory is a learning theory that prioritizes the visible process of changing human behavior. This study aims to construct behavioristic learning theory in the book Bughyatul Ikhwan by Imam Ramli. This study is library research whit a qualitative descriptive approach. The researcher uses bughyatul Ikhwan’s book by Imam Ramli as the main source, while related journals a secondary sources. Then analyzed by content analysis. This study constructs behavioristic learning theory in the book of Bughyatul Ikhwan by Imam Ramli, which includes: First, learning is a process of forming the behavior expected from learning outcomes. According to Imam Ramli, the formation of a child’s behavior can be formed through teaching by being given information regarding how to distinguish and understand what is true. Second, environmental interaction is one of the causes of the formation of children’s behavior attitudes. Imam Ramli chose social interaction with pious people as the right place to hang out for a child. Third, the behavioristic learning theory in Imam Ramli Bughyatul Ikhwan’s book generally has similarities with general psychological theory, only the terms used are different, such as ta’lim (Verbal Information), Ta’dib ( Formation of behavior), Targhib (Reward), Tahdid (threat) dan Tahdzir (warning), social environment interaction and habituation education. Fourth, preventive measures are applied to the explanation in the book Bughyatul Ikhwan by Imam Ramli with Tahdid (threat) dan Tahdzir (warning).